PEMANFAATAN LIMBAH SERBUK GERGAJIAN KAYU ULIN (Eusideroxylon zwageri T & B) UNTUK MENURUNKAN KADAR FECAL COLIFORM AIR SUNGAI - Laksono, Eko Setyo; Kissinger, Kissinger; Suyanto, Suyanto; Achmad, Basir (Universitas Lambung Mangkurat, 2024)
Martapura river water is included in categories that have a fairly high bacterial content, which is 21,333 colonies/100 ml. The optimal value of water quality standards to be met with water treatment businesses is the use of ironwood sawdust waste. Bacteria in water attach most of their lives to suspension particles, so microscopic organisms are also separated or filtered. The purpose of this study was to analyze fecal coliform in river water and analyze the volume of ironwood sawdust to reduce fecal coliform levels in river water. Martapura river water contains the highest fecal 1,800MPN/100ml and the lowest 1,600MPN/100 ml, according to the Minister of the Republic of Indonesia No. 22 of 2021 concerning the implementation of environmental protection and management related to standards, including category two which is used as water tourism facilities/infrastructure, freshwater fish farming, animal husbandry, plant irrigation and other activities requiring the same water quality and use. Ironwood sawdust as much as 25% or 90 grams proved most effective to be used to reduce fecal levels with an average value on the first day of 1,650 MPN/100ml and on the third day with treatment carried out up to indigo 350 MPN/100ml, so that the difference reached a value of 1,300 MPN/100ml.